(untitled) (American Journal of Islam and Society, 2005)
Ever since the West’s initial contact with the East, Muslim women have occupied center stage as highly politicized subjects who the West has claimed to liberate from the oppressive East and who the East has claimed to protect from the hedonistic West. Despite their central role as pawns in this political struggle, women have been strikingly silent subjects. This book belongs to an emerging collection of books that seek to give voice to these silent subjects. Nawal El Saadawi, in her emotionally charged “Foreword,” captures the book’s tone quite well in her expression that “the personal is political” (p. x). Through personal stories, this anthology seeks to dissociate Islam from both terrorism and the oppression of women. Fawzia Afzal-Khan’s anecdotal introduction reveals that her goal is twofold: first, to connect various strands of conversation between Muslim American women from different backgrounds since 9/11, and, second, to enlighten both Muslim and non-Muslim readers of the varied realities of the “Muslim Woman.” This anthology is divided into six sections. Section 1, “Non-Fiction,” contains several personal accounts of Muslim American women’s encounters with 9/11. In her piece “Unholy Alliances,” Afzal-Khan vents her frustration on several targets, including Israel, American foreign policy, Salman Rushdie, women who choose to wear the hijab, as well as the Montclair University Muslim Students’ Association and the Global Studies Institute. Nadia Ali Maiwandi, Zohra Saed, and Wajma Ahmady reflect on the responses they encountered and experienced amidst the Afghan-American community in the aftermath of 9/11. Eisa Nefertari Ulen’s genuinely tolerant article encourages Muslim and non-Muslim women to work together. Writing from her perspective as an African-American convert, she identifies issues of gender and religion as mere smokescreens used by the “oppressor” to separate women (p. 50). Humera Afridi’s witty and refreshing work functions as a social commentary on the climate of New York City after the 9/11 attacks. One of the most edifying pieces is Rabab Abdulhadi’s “Where is Home?” This piece, written as a series of journal entries, captures the struggles of identity faced by an exiled Palestinian woman as she tries to make a home in New York City in the aftermath of 9/11 ...